Understanding the granulation of partial denitrification sludge for nitrite production. (December 2019) - Cao, Shenbin; Du, Rui; Zhang, Hanyu; Peng, Yongzhen
Abstract: Partial-denitrification (PD) has previously been demonstrated to be another pathway for nitrite production, which provides a cost-effective approach for nitrate (NO3 − -N) removal through combing with anammox. In this study, the formation of PD granules was firstly investigated in a sequencing batch reactor (SBR) with influent nitrate of 60 mg N/L. The granulation process was explored via the physicochemical and biological characterization. Sludge granulation initiated within the first 20 days with an average size of 93.7 μm in diameter, it experienced a developing, shaping and matured periods, with a maximum size of 709.3 μm obtained. High nitrite production of PD was always maintained during the granulation with a mean nitrate-to-nitrite transformation ratio (NTR) of 88.3%, and in-situ maximum NO3–N reduction rate of 84.9 mg N/h/g VSS was obtained. Mature PD granules hold an excellent settling property with 5-min sludge volume index (SVI5 ) of 32.0 mL/g MLSS obtained and smooth surface with large amounts of rod bacteria covered. CaCO3 precipitates formed in the PD process played a vital role in the initial granulation, acting as the nucleus for cell attachment. Extracellular polymeric substances (EPS), mainly the proteins (PN) content, was found to be of supreme importance in granules developing and maintaining its structural stability. Besides, the abundance of Flavobacterium and norank_p__Gracilibacteria were revealed to be in accordance with the change of granules size, seemed to contribute to sludge granulation. The developed granule-based PD integrated with anammox process provides an engineering-feasible and economic-favorable solution for industrial nitrate wastewater treatment. Graphical abstract: Image 1 Highlights: Partial denitrification granules were firstly cultivated in sequencing batch reactor. CaCO3 precipitates accelerated the initial granulation by acting as the nucleus. Extracellular polymeric substances were of supreme importance in maintaining granule stability. High nitrite production with transformation ratio of 88.3% was achieved over the operation. Dominant functional groups for granulation and nitrite production were identified.